Adaptive Power Management for Multi-User Indoor LiFi Communication Systems using Evolutionary Algorithms - Saif Ahmed Abed; Nahla Abdul Jalil Salih; Ihsan Jabbar Hasan; Nadhir Ibrahim Abdulkhaleq (P3M Politeknik Negeri Banjarmasin, 2026)
Visible Light Communication (VLC) systems have emerged as a promising alternative to RF-based solutions, especially in electromagnetic-sensitive environments such as hospitals and aircraft cabins. This study presents a MATLAB-based simulation of an indoor VLC setup using corner and center LED array layouts in an emer-gency room scenario. The model supports variations in room length and user density and applies a genetic al-gorithm (GA) for dynamic LED current optimization to improve coverage fairness. This paper proposes an adaptive beam-shaping and power-optimization framework for multi-user indoor LiFi communication systems. The design is particularly suited for environments sensitive to electromagnetic interference (EMI), such as hospitals and emergency rooms, where RF-based systems may pose risks or interfere with medical equipment. Simulation results show that the corner configuration consistently outperformed the center configuration in terms of minimum and average received power, especially in larger rooms (10 m to 12 m) and with higher user numbers (6 to 8). For instance, in the corner case, the mean received power changed from 1.4075×10⁻⁶ to 1.3808×10⁻⁶ W when the number of users increased from 6 to 8, whereas in the center case it dropped from 1.0154×10⁻⁶ to 7.9926×10⁻⁷ W. Additionally, the optimal minimum power improved in larger rooms and with higher user densities, thus helping maintain communication even for the weakest users. The results confirm that GA-based current shaping improves energy efficiency and signal distribution, making this approach valu-able for robust and future-ready VLC applications in emergency scenarios.